Aplikasi Metode Market Basket Analysis dengan Algoritma Apriori untuk Mengetahui Pola Belanja Konsumen pada Online Shop Amerta Fashion - Utami, Iut Tri; Dapa, Rahmila (Indonesian Journal of Applied Statistics, 2023)
In this era of globalization, society has been facilitated in various ways due to advances in technology, one of which is the use of the internet. One of the goals of the continuous development of technology is to meet human needs. According to a global survey conducted by Nielsen Online in 2009, more than 85% of the world's population has used the internet for buying and selling transactions. The increase in purchases made online, especially during this pandemic period, shows that people have begun to be technology literate. The large number and rapid growth of data often overwhelm business actors in processing data so that they are left unorganized, even though the data obtained can produce useful information to support decisions or assist in determining marketing strategies. This difficulty also occur at Online Shop Amerta Fashion. This study uses one of the data mining methods, namely Market Basket Analysis with a priori algorithm which goes through the stages of data collection, formation of association rules, and concluding. Market basket analysis can determine consumer buying patterns and also find out which items are selling well. The results obtained is that consumers of Online Shop Amerta Fashion didn’t only buy 1 item in a transaction. Boyfriend Jeans Highwaist and Wrap Top Summer are 2 types of items that are popularly purchased by consumers so that they become the most influential items in the overall purchasing transactions from Online Shop Amerta Fashion from January 4, 2021 to June 18, 2021.Keywords: data mining; association rules; market basket analysis; Apriori; Online Shop Amerta Fashion